2017
DOI: 10.1111/jvim.14774
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Granulocyte Immunofluorescence Assay Designed for Humans for Detection of Antineutrophil Cytoplasmic Antibodies in Dogs with Chronic Enteropathies

Abstract: BackgroundPerinuclear antineutrophil cytoplasmic antibodies (pANCA) previously have been shown to be serum markers in dogs with chronic enteropathies, with dogs that have food‐responsive disease (FRD) having higher frequencies of seropositivity than dogs with steroid‐responsive disease (SRD). The indirect immunofluorescence (IIF) assay used in previous publications is time‐consuming to perform, with low interobserver agreement.Hypothesis/ObjectivesWe hypothesized that a commercially available granulocyte IIF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Accordingly, CRP was herein found high in the sera of only four out of 17 dogs, regardless of the final diagnosis, without differences among the dogs affected by different forms of CE, including those dogs affected by PLE. In one study (48), the seropositivity for pANCA discriminated IRE/NRE from other causes of diarrhea, with a sensitivity of 51% and a specificity of 83%, while in other studies the pANCA was found higher in sera of dogs with FRE than in sera of those affected by IRE/NRE (Se 61-62%; Sp 77-100%) (49,50). However, similar to serum CRP, seropositivity for pANCA can be also detected with other inflammatory conditions (51).…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, CRP was herein found high in the sera of only four out of 17 dogs, regardless of the final diagnosis, without differences among the dogs affected by different forms of CE, including those dogs affected by PLE. In one study (48), the seropositivity for pANCA discriminated IRE/NRE from other causes of diarrhea, with a sensitivity of 51% and a specificity of 83%, while in other studies the pANCA was found higher in sera of dogs with FRE than in sera of those affected by IRE/NRE (Se 61-62%; Sp 77-100%) (49,50). However, similar to serum CRP, seropositivity for pANCA can be also detected with other inflammatory conditions (51).…”
Section: Discussionmentioning
confidence: 94%
“…Seropositivity for pANCA (and also pANCA titers) is higher in dogs with FRE (61%‐62%) than in those with IRE or NRE (0%‐37%) 95, 99, 100, 101. However, pANCA seropositivity is not specific for CIE and also can occur with other immune‐mediated, infectious, or neoplastic diseases 101, 102.…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
“…Perinuclear anti-neutrophilic cytoplasmic antibodies (pANCA) are serum autoantibodies against neutrophil granule components (eg, nuclear histone, proteinase 3, myeloperoxidase) and suspected crossreactivity with a gastrointestinal bacterial antigen 98 that can be detected by indirect immunofluorescence assays. 98,99 Seropositivity for pANCA (and also pANCA titers) is higher in dogs with FRE (61%-62%) than in those with IRE or NRE (0%-37%…”
Section: Perinuclear Anti-neutrophilic Cytoplasmic Antibodiesmentioning
confidence: 99%
“…It is, therefore, prudent to always correlate the positivity of these tests with clinical findings. Of note, pANCA testing has recently been shown to correlate well with an indirect immunofluorescent method using human granulocytes as antigens, which is a clear advantage for further commercialization efforts 39 …”
Section: Perinuclear Anti‐neutrophilic Cytoplasmic Antibodies (Panca)mentioning
confidence: 98%